Cost-Effectiveness Analysis Of The Use Of Ciprofloxacin And Levofloxacin Antibiotics For Urinary Tract Infections In BPJS Inpatients At RSUD Dr. Moewardi Surakarta - Annisa Nurulita Dyah Savitri; Kharisma Jayak Pratama; Aprilia Puteri Santika (International Journal of Health Engineering and Technology, 2026)
Urinary tract infections (UTIs) are a significant health burden in Indonesia, with high antibiotic therapy costs in BPJS inpatients. This study aims to analyze the cost-effectiveness of ciprofloxacin versus levofloxacin in BPJS inpatient UTI patients at Dr. Moewardi Surakarta Hospital from January to June 2025. This study used retrospective quantitative descriptive research with secondary data from medical and financial records; the population of all cases met the criteria (n=127) using total sampling. Data extraction instruments were demographic variables, effectiveness (temperature, length of hospitalization), and direct medical costs; CEA analysis via ACER, ICER, and Mann-Whitney test (p<0.05). The results showed equivalent effectiveness (ciprofloxacin 36.78%; levofloxacin 35%), ACER of ciprofloxacin Rp470,910 lower than levofloxacin Rp621,220, negative ICER Rp-2,451,792, with no significant difference (p>0.05). Conclusion: Both therapies are economically equivalent, supporting the optimization of JKN.